Superovulation of mares: Review - Gonçalves, Priscyla Lorena de Sá; Alcantara, Luíza Paula Araújo; Silva, Aluísio Otávio Almeida (Pubvet, 2022)
Superovulation is an accepted biotechnology in mares, which recognizes in countable gains for the species reproduction, as the increase in fertility rates, highest possibilities of pregnancy for frozen and sexed semen, superior of sub fertile stallions, increase in the rate of gain embryonic development, anticipation or prognosis of the first ovulation of the year, excellent numbers of embryos for cryopreservation and multiplication in the number of follicles for oocyte collection. Thus, it is essential that a veterinarian has knowledge on this subject to work in aquiculture. This work aims to carry out a literature review on the main approaches to hormonal protocols used in the induction of superovulation in mares. As a result, it was observed that working with mares’s superovulation protocols, in addition to enabling the enhancement of their reproductive capacity, can also offer greater profitability for the producer.